Overview of greenhouse gas emission accounting in the Brazilian industrial sector (Sustainability in Debate, 2016)
Brazil’s National Policy on Climate Change (NPCC) defines the need to monitor, report and verify greenhouse gas (GHG) emissions in the Brazilian industrial sector. The aim of this study is to provide an overview of GHG emission accounting of processing industries, regarding the voluntary participation of the companies to meet the goals established by the NPCC. The authors used the inventories from the GHG Protocol Brazil and from the Carbon Disclosure Project (CDP), dated between 2008 and 2014. Results show that processing industries represent 25,1% of the companies that participated of the GHG Protocol and 22,3% of the CDP, in 2014. The register of processing industry inventories increases 15% per year and the extrapolation of this information shows that the goal of reporting GHG emissions in the Brazilian public record can be reached by 2020.